Group A Streptococcal Puerperal Sepsis: Historical Review and 1990s Resurgence - Lawrence Nathan; Kenneth J. Leveno (Hindawi Limited, 1994)
There appears to be a resurgence of puerperal sepsis due to a historically important pathogen, group A β-hemolytic streptococcus.